A taxonomic revision of Cyclosorus subgenus Cyclosoriopsis (Thelypteridaceae) from China. Issue 5 (5th June 2013) - LI, Zhong‐Yang; HE, Zhao‐Rong; ZHANG, Xian‐Chun
Abstract: This paper deals with species of the genus Cyclosorus subgenus Cyclosoriopsis (Thelypteridaceae) from China, which is characterized by goniopteroid venation and unicellular glands on sporangial stalks. Morphological study of specimens and living plants reveals that venation and glands/glandular hairs on laminae are the most important diagnostic characters for species identification. Twenty‐two species are recognized, including seven species endemic to China. Fifty species names are newly reduced to synonyms. A key to species from China, description, and distribution map of each species are provided. Three species are treated as dubious species, and 22 species are treated as putative hybrids.